2022
DOI: 10.3390/cells11030484
|View full text |Cite
|
Sign up to set email alerts
|

Male Pheromones Induce Ovulation in Female Honeycomb Groupers (Epinephelus merra): A Comprehensive Study of Spawning Aggregation Behavior and Ovarian Development

Abstract: This study characterizes the spawning phenomena of the honeycomb grouper (Epinephelus merra), which is a lunar-synchronized spawner that spawns a few days after full moon. To elucidate the aggregation characteristics of wild honeycomb groupers, the numbers of males and females at the spawning grounds were counted before and after the full moon. Approximately 20 males were consistently observed at the spawning grounds throughout the study period. Females appeared several days after full moon and rapidly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…To avoid visual cues, the structure of the rearing system was designed so the females in the lower aquarium could not visually recognize the males in the upper aquarium ( Figure 2 ). The results indicated that final maturation progressed and ovulation occurred in mature females exposed to the rearing water of mature males, but not that of the control tank [ 51 ]. These results demonstrate that the execution of FOM and ovulation in honeycomb grouper females requires pheromones from mature males.…”
Section: Final Maturation and Spawningmentioning
confidence: 99%
“…To avoid visual cues, the structure of the rearing system was designed so the females in the lower aquarium could not visually recognize the males in the upper aquarium ( Figure 2 ). The results indicated that final maturation progressed and ovulation occurred in mature females exposed to the rearing water of mature males, but not that of the control tank [ 51 ]. These results demonstrate that the execution of FOM and ovulation in honeycomb grouper females requires pheromones from mature males.…”
Section: Final Maturation and Spawningmentioning
confidence: 99%